Jesus, Mark and Q : the Teaching of Jesus and Its Earliest Records. - Labahn, Michael (Library of New Testament studies., 2001)
The first part of this collection is devoted to one of the key questions of the 'Synoptic Problem': the literary and christological relationship between Mark and Q. The second part deals with the 'Third Quest' for the historical Jesus, concentrating on his teaching and its cultural context. These interrelated themes each attract detailed analysis of their methodology as well as their impact on New Testament studies generally, providing a very useful introduction to the state of research in these important fields.